Profesinalisasi Birokrasi dalam Pelayanan Publik - Yunus, Yasril (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2002)
The service of face to face birocracy appear a stigma come to a stadium confusing society, so that it becomes a chronic bureaupathology, and even lead to an administrative inertia, that is a condition of uncapability birocracy to act professionally. Professioanlism will come true if there is a fitness between bureucratic competency and task-requerement, and it can be developed if there is political will of a government.To change a bureucracy philosophy, it is necessary to reposite vision and mission of public bureucracy, norms and structure, and bureucracy procedure moved from rule governance paradigm provided the best services for Key Words: profesionalisasi, birokrasi, pelayanan publik